2022
DOI: 10.34108/eujhs.915320
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Reading Food Label Behaviour in University Students

Abstract: Besin etiketi okuma, bireylerin yeterli ve dengeli beslenmelerinde önemli rol oynamaktadır. Çalışmanın amacı; lisans öğrencilerinin besin etiketi okuma davranışının incelenmesi ve satın almada en fazla önem verilen faktörleri belirlemektir. Çalışma Şubat-Mayıs 2019 tarihleri arasında Türkiye’de yapılmıştır. Dört kısım olarak hazırlanan anketin ilk bölümünde katılımcıların demografik özellikleri tespit edilmiştir. Diğer bölümlerin bir kısmında 5’li, bir kısmında 3’lü Likert ölçeği kullanılarak sorular sorulmuşt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…In the study, it was determined that there was no significant difference between the average score of male students' problem solving skills and the average score of female students. In the literature, there are studies that determine that the perception of problem solving in university students does not differ according to gender (Alver, 2005;Bilge & Arslan, 2000;Can, Öner & Çelebi, 2009;Diker-Coşkun, Garipoğlu, & Tosun, 2014;Dündar, 2009;Elkin & Karadağlı , 2015;Saracaloğlu et al, 2009;Tümkaya & İflazoğlu, 2000;Yılmaz et al, 2009). However, some studies also found a significant difference between gender and problem-solving skills (Barahmand, 2010;Otacıoğlu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, it was determined that there was no significant difference between the average score of male students' problem solving skills and the average score of female students. In the literature, there are studies that determine that the perception of problem solving in university students does not differ according to gender (Alver, 2005;Bilge & Arslan, 2000;Can, Öner & Çelebi, 2009;Diker-Coşkun, Garipoğlu, & Tosun, 2014;Dündar, 2009;Elkin & Karadağlı , 2015;Saracaloğlu et al, 2009;Tümkaya & İflazoğlu, 2000;Yılmaz et al, 2009). However, some studies also found a significant difference between gender and problem-solving skills (Barahmand, 2010;Otacıoğlu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…4 Üniversite öğrencilerinde besin etiketi okuma davranışı üzerine yapılmış bir çalışmada, besin etiketinde yer alan toplam yağ ve doymuş/doymamış yağ içeriğine dikkat etme konusunda cinsiyetler arasında anlamlı bir fark bulunurken, kadın katılımcıların besinlerin şeker içeriğine daha fazla önem verdikleri saptanmıştır. 26 Çalışmamızda, "Toplam yağ", "vitamin", "şeker", "az yağlı/yağsız" ve "sağlık problemi ile ilişkisi" etiket bilgilerinin kontrol edilme sıklığı, kadın ebeveynlerde erkek ebeveynlere göre istatistiksel olarak anlamlı bir seviyede daha yüksek bulunmuştur. Bu durum, kadın ebeveynlerin çocukları için besin seçerken, erkek ebeveynlere kıyasla daha fazla besin içerik bilgisine dikkat ettiklerini gösterir.…”
Section: Discussionunclassified
“…It has been determined that individuals who read the food label pay attention to their regular meal consumption and consume less unhealthy foods, while they consume more healthy foods [29]. In the study of Arslan et al (2022) examining the food label reading behavior of university students; It has been determined that students studying in the field of health pay more attention to some nutritional information (calories, total fat, sugar) written on the label [30]. It is thought that increasing the level of knowledge about health contributes to a healthy diet.…”
Section: Discussionmentioning
confidence: 99%